Penanganan Anak Manja dengan Bijak: Strategi Orangtua yang Efektif - Didit Darmawan; Masfufah Masfufah (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2023)
This research investigates the phenomenon of "spoiled children" and its implications for child development with an emphasis on analyzing the stages of cognitive, emotional and social development that can be affected by over-pampering. Through an exploration of the characteristics of spoiled children, such as resistance to the word "no" and self-orientation, this study reveals that spoiling behaviors can contribute to immaturity, dependency, and difficulties in sharing. The results highlight the need for prevention and countermeasures, including setting healthy boundaries, reinforcing positive behaviors, and improving communication between parents and children. The implementation of these measures is expected to help reduce the negative impact of spoiling children on their development.